The last spark - Van Vu Kieu Thien Kim (2015)
This document is the report for Van Vu Kieu Thien Kim’s Final Year Project, a video game named The Last Spark. The purpose of this document is to provide a summarized and structured presentation of the game concept and the game development process during the last academic year. The Last Spark is a journey of a small little girl in pursuit of her own happiness. It is a third person psychological horror game about immersion, discovery and living through a nightmare. Set in the imagination of the girl, the game is her journey to survive and conquer fear in order to discover what she deeply treasures. The Last Spark addresses the psychological side of a human being. The game was designed not only for entertainment purposes but also to bring the same quality of a good Expressionist art piece.